2021
DOI: 10.12998/wjcc.v9.i27.8051
|View full text |Cite
|
Sign up to set email alerts
|

Bridging therapy and direct mechanical thrombectomy in the treatment of cardiogenic cerebral infarction with anterior circulation macrovascular occlusion

Abstract: BACKGROUND Intravenous thrombolysis is an important treatment for cerebral infarction. However, it is difficult to achieve good results if the patient is complicated with anterior circulation macrovascular occlusion. In addition, the vascular recanalization rate is low, so mechanical thrombectomy, that is, bridging therapy, is needed AIM To investigate the efficacy and safety of bridging therapy and direct mechanical thrombectomy in the treatment of cardiogenic cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Although arterial thrombolysis, as an interventional method, causes certain trauma, the proportion of patients with postoperative complications after bridging therapy did not increase significantly compared with those treated with intravenous thrombolysis alone, suggesting that the combined treatment is safe [20]. Previous studies have found that bridging therapy can safely treat patients with cardiogenic cerebral infarction complicated with anterior circulation macrovascular occlusion, contributing to good vascular recanalization effects and patient prognosis, as well as improved Journal of Immunology Research neurological function of patients [21], which corroborates our observations. Inflammation, which is positively correlated with the severity of cerebral infarction, is essential in the pathogenesis and progression of the disease and acts as an independent pathogenic factor for clinical prognosis and disease outcome assessment of patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although arterial thrombolysis, as an interventional method, causes certain trauma, the proportion of patients with postoperative complications after bridging therapy did not increase significantly compared with those treated with intravenous thrombolysis alone, suggesting that the combined treatment is safe [20]. Previous studies have found that bridging therapy can safely treat patients with cardiogenic cerebral infarction complicated with anterior circulation macrovascular occlusion, contributing to good vascular recanalization effects and patient prognosis, as well as improved Journal of Immunology Research neurological function of patients [21], which corroborates our observations. Inflammation, which is positively correlated with the severity of cerebral infarction, is essential in the pathogenesis and progression of the disease and acts as an independent pathogenic factor for clinical prognosis and disease outcome assessment of patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nie et al reported better results with BT in patients with basilar artery occlusions [ 40 ]. In two studies, the efficacy of BT was evaluated in patients with a cardioembolic stroke, showing no differences and a worse functional outcome in the BT group, respectively [ 41 , 42 ]. There is also no consensus regarding tandem carotid occlusions, with some data supporting a better prognosis with BT and others showing a higher mortality in this group [ 32 , 38 ].…”
Section: Discussionmentioning
confidence: 99%